Community Acquired Pneumonia pada Lansia - Harry Pasca Rullian; Irvan Medison; Dessy Mizarti; Dewi Wahyu F (Jurnal Syntax Admiration, 2024)
Community Acquired Pneumonia (CAP) causes high morbidity and mortality worldwide, especially in elderly patients. Establishing a diagnosis of CAP in elderly patients is a challenge for clinicians considering that the symptoms are not always typical and specific. The following is a case report of a 72-year-old woman with a diagnosis of CAP without any previous complaints of shortness of breath. There is an infiltrate on chest X-ray and symptoms of cough, productive sputum, fever, and leukocytosis confirm the diagnosis of CAP in this patient. The patient was given antibiotic levofloxacin 1 x 750 mg until Klebsiella pneumoniae was found in the sputum culture results.